Sedation assessment in a mobile intensive care unit: a prospective pilot-study on the relation of clinical sedation scales and the bispectral index - Prottengeier, Johannes; Moritz, Andreas; Heinrich, Stefan; Gall, Christine; Schmidt, Joachim (Critical Care, 2014)
The critically-ill undergoing inter-hospital transfers commonly receive sedatives in continuation of their therapeutic regime or to facilitate a safe transfer shielded from external stressors. While sedation assessment is well established in critical care in general, there is only little data available relating to the special conditions during patient transport and their effect on patient sedation levels. The aim of this prospective study was to investigate the feasibility and relationship of clinical sedation assessment (Richmond Agitation-Sedation Scale (RASS)) and objective physiological monitoring (bispectral index (BIS)) during patient transfers in our Mobile-ICU.The levels of sedation of 30 pharmacologically sedated patients were evaluated at 12 to 17 distinct measurement points spread strategically over the course of a transfer by use of the RASS and BIS. To investigate the relation between the RASS and the BIS, Spearman's squared rank correlation coefficient (?(2)) and the Kendall's rank correlation coefficient (?) were calculated. The diagnostic value of the BIS with respect to the RASS was investigated by its sensitivity and positive predictive value for possible patient awakening. Therefore, measurements were dichotomized considering a clinically sensible threshold of 80 for BIS-values and classifying RASS values being nonnegative.Spearman's rank correlation resulted to ?(2) = 0.431 (confidence interval (CI) = 0.341 to 0.513). The Kendall's correlation coefficient was calculated as ? = 0.522 (CI = 0.459 to 0.576). Awakening of patients (RASS >= 0) was detected by a BIS value of 80 and above with a sensitivity of 0.97 (CI = 0.89 to 1.00) and a positive predictive value of 0.59 (CI = 0.45 to 0.71).Our study demonstrates that the BIS-Monitor can be used for the assessment of sedation levels in the intricate environment of a Mobile-ICU, especially when well-established clinical scores as the RASS are impracticable. The use of BIS is highly sensitive in the detection of unwanted awakening of patients during transfers.
EVALuna2:5483